Sistem Penunjang Keputusan Jabatan Fungsional Akademik Tenaga Pendidik di STIE Kesatuan - Pingky Dezar Zulkarnain; Yanto Hermawan (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2021)
One important part of the rank of an educator at STIE Kesatuan is required to understand the processes in applying for promotion by completing complete documents, consisting of education and teaching, scientific work, community service and support. So far, the process of increasing the functional position of educators is based on the results of the processing carried out based on the work unit in the HRD. For the sake of appropriateness of the process of increasing the academic position of lecturers and the suitability of the points required, a support system for the decision to increase in academic functional positions is made for educators. The data used are in the form of previous rank files along with educational and teaching files, scientific papers, community service and support. The econometric analysis method is used to calculate statistically. The test results carry out structural and functional checks to determine whether the system being made is in accordance with the design or not. Keywords: Decision support systems, Data flow diagram